TP53 mutations predict for poor survival in de novo diffuse large B-cell lymphoma of germinal center subtype - Zainuddin, Norafiza; Berglund, Mattias; Wanders, Alkwin; Ren, Zhi-Ping; Amini, Rose-Marie; Lindell, Monica; Kanduri, Meena; Roos, Göran; Rosenquist, Richard; Enblad, Gunilla (Elsevier Limited, 2008)
Presence of TP53 mutations has been associated with poor prognosis in diffuse large B-cell lymphoma (DLBCL), although this has remained controversial. The TP53 codon 72 polymorphism has shown negative impact on cancer survival, but this has not been analyzed in DLBCL. Furthermore, the MDM2 SNP309 has been associated with earlier age of onset in DLBCL. Here, we investigated the clinical impact of TP53 mutations,MDM2SNP309 and TP53 codon 72 polymorphisms on survival in DLBCL of germinal center (GC) and non-GC subtypes. Thirteen of the 102 (12.7%) patients displayed TP53 mutations. Overall, TP53 mutations had a significant effect on lymphoma-specific survival (LSS, P = 0.009) and progression-free survival (PFS, P = 0.028). In particular, inferior survival was observed in TP53-mutated DLBCLs of GC subtype (LSS, P = 0.002 and PFS, P = 0.006). Neither MDM2 SNP309 nor the TP53 codon 72 polymorphism had an impact on age of onset or survival. Altogether, our data suggests that TP53 mutations are associated with poor outcome in GC-DLBCL patients.